The role of leadership in increasing effectiveness national defense human resource management - Kustiawan, Bambang; Ghazalie, Ghazalie (Goodwood Publishing, 2025)
Purpose: This study aims to explain the effectiveness of leadership in HR management in the defense sector, as well as its impact on organizational performance and long-term consequences. Research Methodology: Using a qualitative approach based on literature studies, this study analyzes data from credible academic and non-academic sources. The focus is on leadership strategies in improving the effectiveness of defence human resources through comparative studies from various countries, including the Indonesian Armed Forces and the Australian Defence Force. Results: Using a qualitative approach based on literature studies, this study analyzes data from credible academic and non-academic sources. The focus is on leadership strategies in improving the effectiveness of defence human resources through comparative studies from various countries, including the Indonesian Armed Forces and the Australian Defence Force.